Velocity encoding and velocity compensation for multi-spoke RF excitation - Schmidt, Simon; Flassbeck, Sebastian; Bachert, Peter; Ladd, Mark E.; Schmitter, Sebastian (Magnetic resonance imaging, 2020)
Purpose - To investigate velocity encoded and velocity compensated variants of multi-spoke RF pulses that can be used for flip-angle homogenization at ultra-high fields (UHF). Attention is paid to the velocity encoding for each individual spoke pulse and to displacement artifacts that arise in Fourier transform imaging in the presence of flow. - Theory and methods - A gradient waveform design for multi-spoke excitation providing an algorithm for minimal TE was proposed that allows two different encodings. Such schemes were compared to an encoding approach that applies an established scheme to multi-spoke excitations. The impact on image quality and quantitative velocity maps was evaluated in phantoms using single- and two-spoke excitations. Additional validation measurements were obtained in-vivo at 7 T. - Results - Phantom experiments showed that keeping the first gradient moment constant for all k-space lines eliminates any displacements in phase-encoding and slice-selection direction for all spoke pulses but leads to artifacts for non-zero velocity components along readout direction. Introducing variable but well-defined first gradient moments in the phase-encoding direction creates displacements along the velocity vector and thus minimizes velocity-induced geometrical distortions. Phase-resolved mean volume flow in the ascending and descending aorta obtained from two-spoke excitation showed excellent agreement with single-spoke excitation over the cardiac cycle (mean difference 0.8 ± 16.2 ml/s). - Conclusions - The use of single- and multi-spoke RF pulses for flow quantification at 7 T with controlled displacement artifacts has been successfully demonstrated. The presented techniques form the basis for correct velocity quantification and compensation not only for conventional but also for multi-spoke RF pulses allowing in-plane B1+ homogenization using parallel transmission at UHF.